Pengaruh Minat Dalam Memilih Program Keahlian Akuntansi Terhadap Prestasi Belajar Siswa Kelas X di SMK Negeri 1 Batudaa Kabupaten Gorontalo - Sarmira M Abas; Usman Moonti; Ivan Rahmat Santoso; Melizubaida Mahmud; Agil Bahsoan; Sudirman Sudirman (State University of Gorontalo, 2023)
The research applied a total population sampling technique. As a result, the entire population (41 students) was selected as the sample of this research. Research data were collected through observations, questionnaires, and documentation. The findings reveal that there is a positive correlation between rising students’ interest in selecting an accounting expertise program and rising students learning achievement, with the correlation coefficient value of the previously obtained regression model of 0,697. This value indicated that 67,9% of the variables effecting students’ learning achievement in the tenth grade at SMK Negeri 1 Batudaa are influenced by students’ interest in selecting an accounting expertise program, while the remaining 30,3% are influenced by other variables that are not examined in this study.